Analysis of Company Financial Performance Before and After Initial Public Offering (IPO) on the Indonesia Stock Exchange - Wildan Yahya, Muhammad; Dahlia Iryani, Lia; Martanti Endah Lestari , Retno (Tazkia Islamic University College, 2023)
This study aims to analyze (1) the company's financial performance before and after (2) Initial Public Offering (IPO) in companies that conducted an IPO in 2018. The company's financial performance is measured by (3) financial ratios consisting of: Current Ratio (CR) , Debt to Equity Ratio (DER), Total Assets Turnover (TATO), and Return On Euity (ROE). The sample used in this study were 8 companies. The sample was selected using purposive sampling. The type of research used in this research is descriptive with SPSS 25. Data analysis consists of descriptive statistics, normality test using Kolmogrov Smirnov test and hypothesis testing using Paired Sample T-Test. Based on the test using the Paired Sample T-Test, it shows that the company's financial performance after the IPO there is a difference in the salvoability ratio which is proxied by the Debt to Equity Ratio (DER). While the ratios that do not experience any difference are the liquidity ratio proxied by the Current Ratio (CR), the activity ratio as proxied by Total Assets Turnover (TATO) and the profitability ratio as proxied by Return On Equity (ROE).